2015
DOI: 10.1242/jcs.167049
|View full text |Cite
|
Sign up to set email alerts
|

Differing roles of pyruvate dehydrogenase kinases during mouse oocyte maturation

Abstract: Pyruvate dehydrogenase kinases (PDKs) modulate energy homeostasis in multiple tissues and cell types, under various nutrient conditions, through phosphorylation of the α subunit (PDHE1α, also known as PDHA1) of the pyruvate dehydrogenase (PDH) complex. However, the roles of PDKs in meiotic maturation are currently unknown. Here, by undertaking knockdown and overexpression analysis of PDK paralogs (PDK1-PDK4) in mouse oocytes, we established the site-specificity of PDKs towards the phosphorylation of three seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 52 publications
4
34
0
Order By: Relevance
“…Of note, ectopic expression of SIRT4 results in the very similar phenotypes as we observed in oocytes overexpressing pyruvate dehydrogenase kinase 3 (PDK3) (Hou et al., 2015). Moreover, it has been reported that PDKs expression was altered in multiple cell types with SIRT4 depletion (Nasrin et al., 2010; Tao, Zhang, Ling, McCall, & Liu, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of note, ectopic expression of SIRT4 results in the very similar phenotypes as we observed in oocytes overexpressing pyruvate dehydrogenase kinase 3 (PDK3) (Hou et al., 2015). Moreover, it has been reported that PDKs expression was altered in multiple cell types with SIRT4 depletion (Nasrin et al., 2010; Tao, Zhang, Ling, McCall, & Liu, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…PDH is able to modulate tricarboxylic acid (TCA) cycle in cells, producing ATP and many biosynthetic intermediates in mammalian oocytes. We have discovered that the phosphorylation status of PDHE1α subunit is associated with metabolic control and meiotic apparatus in mouse oocytes (Hou et al., 2015). We therefore asked whether the PDHE1α phosphorylation, at least in part, mediates the effects of SIRT4 on oocyte maturation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations